Pathogenetic determinants in Kawasaki disease: the haematological point of view - Domenico Del Principe; Donatella Pietraforte; Lucrezia Gambardella; Alessandra Marchesi; Isabella Tarissi de Jacobis; Alberto Villani; Walter Malorni; Elisabetta Straface (2017)
Abstract Kawasaki disease is a multisystemic vasculitis that can result in coronary artery lesions. It predominantly affects young children and is characterized by prolonged fever, diffuse mucosal inflammation, indurative oedema of the hands and feet, a polymorphous skin rash and non‐suppurative lymphadenopathy. Coronary artery involvement is the most important complication of Kawasaki disease and may cause significant coronary stenosis resulting in ischemic heart disease. The introduction of intravenous immunoglobulin decreases the incidence of coronary artery lesions to less than 5%. The etiopathogenesis of this disease remains unclear. Several lines of evidence suggest that an interplay between a microbial infection and a genetic predisposition could take place in the development of the disease. In this review, we summarize the state of the art of pathogenetic mechanisms of Kawasaki disease underscoring the relevance of haematological features as a novel field of investigation.